2020
DOI: 10.1029/2020ja028209
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of Solar Wind, Magnetosheath, and Magnetotail Plasma and Field Properties: 12+ Years of THEMIS Observations and MHD Simulations

Abstract: The solar wind plasma is a major plasma source for the Earth's magnetosphere, which has a strong influence on the magnetotail plasma and field properties. The relative importance of different plasma entry mechanisms and pathways is largely determined by the solar wind conditions. Therefore, the spatial and temporal dependence of magnetotail plasma and field properties under different kinds of solar wind conditions is critically important for understanding the Earth's magnetosphere. This study presents a statis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 99 publications
4
15
0
Order By: Relevance
“…For non-peaks, the trend is opposite: The maximum temperature, ∼3 keV is observed near dawn. The latter dawn-dusk asymmetry is consistent with previous THEMIS observations of electron temperature that attributed the asymmetry to the eastward electron drift and simultaneous adiabatic energization (e.g., Dubyagin et al, 2016;Ma et al, 2020;Wang et al, 2012). This contrast between the peaks' and non-peaks' trends results in the percent change being positive (∼300%) in the dusk sector and negative (∼−100%) in the dawn sector.…”
Section: Automated Event Detection Algorithm and Bbf Selection Criteriasupporting
confidence: 89%
“…For non-peaks, the trend is opposite: The maximum temperature, ∼3 keV is observed near dawn. The latter dawn-dusk asymmetry is consistent with previous THEMIS observations of electron temperature that attributed the asymmetry to the eastward electron drift and simultaneous adiabatic energization (e.g., Dubyagin et al, 2016;Ma et al, 2020;Wang et al, 2012). This contrast between the peaks' and non-peaks' trends results in the percent change being positive (∼300%) in the dusk sector and negative (∼−100%) in the dawn sector.…”
Section: Automated Event Detection Algorithm and Bbf Selection Criteriasupporting
confidence: 89%
“…For non-peaks, the trend is opposite: the maximum temperature, ~3 keV is observed near dawn. The latter dawn-dusk asymmetry is consistent with previous THEMIS observations of electron temperature that attributed the asymmetry to the eastward electron drift and simultaneous adiabatic energization (e.g., Wang et al, 2012;Dubyagin et al, 2016;Ma et al, 2020). This contrast between the peaks' and non-peaks' trends results in the percent difference being positive (~300-400%) in the dusk sector and negative (~-100%) in the dawn sector.…”
Section: Automated Event Detection Algorithm and Bbf Selection Criteriasupporting
confidence: 89%
“…It has been demonstrated that magnetic reconnection cannot provide sufficient adiabatic heating unless the plasma beta is much smaller than unity . However, the typical magnetosheath plasma beta is about one (Ma et al, 2020), leading to the speculation that the KH instability may be responsible for an additional nonadiabatic heating source (Moore et al, 2016;Moore et al, 2017;Nykyri et al, 2021a;Nykyri et al, 2021b). But, as an ideal instability (i.e., the onset of the instability does not break the "frozen-in" condition), the MHD description of the KH instability conserves specific entropy, meaning no nonadiabatic heating source.…”
Section: Resultsmentioning
confidence: 99%